(untitled) (Research, Society and Development, 2020)
This work aims to analyze the importance of didactic design for an online discipline in health. This is a theoretical study of reflective analysis on the importance of didactic Design for an online discipline in health and its teaching strategies with a view to proposing an interactive teaching. It is based on a review of narrative literature with discussion of the following points: Pedagogical strategies and expected results and the way of evaluating activities. Health professors working in online disciplines need to act as a knowledge mediator with students seeking knowledge. Interactive activities and content are designed for collaborative learning. Given this perspective, it is understood that the development of Didactic Design must be constantly built with a view to improving the distance learning process, the content format and the use of the tools of the virtual learning environment.